Specific features of tuberculosis in the child with concurrent conditions - T. E. Tyulkova; Yu. P. Chugaev; T. N. Vidanov (Туберкулез и болезни лёгких)
The clinical case demonstrated the intermittent course of primary tuberculosis caused by multiple drug resistant mycobacteria in 8 year old child with concurrent disorders of CNS and locomotor apparatus and living in the social institution of the closed type. The disease was detected in 2 years after the early period of primary tuberculous infection and administered preventive treatment by two anti-tuberculosis drugs. The disease was diagnosed during examination due to aspiration pneumonia with expressed clinical manifestations. Treatment of aspiration pneumonia and multiple drug resistant pulmonary tuberculosis was successfully completed.